Please explain more your question
Answer:
m∠EGC=70°
Step-by-step explanation:
we know that
The measure of the inner angle is the semi-sum of the arcs comprising it and its opposite
so
m∠EGC=(1/2)[arc EC+arc DF]
<u><em>Find the value of x</em></u>
we have
m∠EGC=(7x+7)°
arc EC=50°
arc DF=10x°
substitute and solve for x
(7x+7)°=(1/2)[50°+10x°]
14x+14=50+10x
14x-10x=50-14
4x=36
x=9
<u><em>Find the measure of angle EGC</em></u>
m∠EGC=(7x+7)°
substitute the value of x
m∠EGC=(7(9)+7)°=70°
Answer:
1st: 3*root6 + 5
2nd: 35*root2 + 115
3rd: 24*root2 - 20*root6 + 15*root3 - 18
4th: 17*root6 - 38
5th: 13*root10 - 42
Step-by-step explanation:
To simplify these expressions we need to use the distributive property:
(a + b) * (c + d) = ac + ad + bc + bd
So simplifying each expression, we have:
1st.
(2 root 2 + root 3 ) ( 2 root 3 - root 2)
= 4*root6 - 2*2 + 2*3 - root6
= 3*root6 - 4 + 9
= 3*root6 + 5
2nd.
(root 5 + 2 root 10) (3 root 5 + root 10)
= 3 * 5 + root50 + 6*root50 + 2*10
= 15 + 5*root2 + 30*root2 + 100
= 35*root2 + 115
3rd.
(4 root 6 - 3 root 3) (2 root 3 - 5)
= 8*root18 - 20*root6 - 6*3 + 15root3
= 24*root2 - 20*root6 + 15*root3 - 18
4rd.
(6 root 3 - 5 root 2 ) (2 root 2 - root 3)
= 12*root6 - 6*3 - 10*2 + 5*root6
= 17*root6 - 18 - 20
= 17*root6 - 38
5th.
(root 10 - 3 ) ( 4 - 3 root 10)
= 4*root10 - 3*10 - 12 + 9*root10
= 13*root10 - 30 - 12
= 13*root10 - 42
Answer:
-8
Step-by-step explanation:
when you substitute -8 for b it is -4(-8)+3=35
-4(-8) is 32 and 32+3=35
Boom.
also btw need help give brainliest
ABCD 1234 AEIOU = meow meow i’m not a cow who who